Biotin Protein Ligase Is a Target for New Antibacterials - Jiage Feng; Ashleigh S. Paparella; Grant W. Booker; Steven W. Polyak; Andrew D. Abell (MDPI AG, 2016)
There is a desperate need for novel antibiotic classes to combat the rise of drug resistant pathogenic bacteria, such as Staphylococcus aureus. Inhibitors of the essential metabolic enzyme biotin protein ligase (BPL) represent a promising drug target for new antibacterials. Structural and biochemical studies on the BPL from S. aureus have paved the way for the design and development of new antibacterial chemotherapeutics. BPL employs an ordered ligand binding mechanism for the synthesis of the reaction intermediate biotinyl-5'-AMP from substrates biotin and ATP. Here we review the structure and catalytic mechanism of the target enzyme, along with an overview of chemical analogues of biotin and biotinyl-5'-AMP as BPL inhibitors reported to date. Of particular promise are studies to replace the labile phosphoroanhydride linker present in biotinyl-5'-AMP with alternative bioisosteres. A novel in situ click approach using a mutant of S. aureus BPL as a template for the synthesis of triazole-based inhibitors is also presented. These approaches can be widely applied to BPLs from other bacteria, as well as other closely related metabolic enzymes and antibacterial drug targets.